1976
DOI: 10.1037/0022-006x.44.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Homosexuality: The ethical challenge.

Abstract: It is suggested that behavior therapists have not attended sufficiently to the factors influencing the desire of some homosexuals to change their sexual orientation. Therapists of all persuasions constantly make decisions for their voluntary clients, encompassing both the goals of therapy and the means to be used to achieve those goals. A perusal of the psychotherapy and behavior therapy literature indicates that therapists generally regard homosexuality as undesirable, if not pathological. Since professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 5 publications
1
84
0
Order By: Relevance
“…They claimed a 27% ''cure'' rate with psychoanalysis, but when challenged a decade later to produce a ''cured'' patient, they were unable to do so (Tripp, 1987). 27 Although practitioners of aversion therapy in the 1960s also claimed ''cures,'' by the 1970s behavioral therapists admitted that few of their patients managed to stay ''converted'' for very long (Bancroft, 1974;Davison, 1976).…”
Section: Homosexuality As Psychiatric Diagnosismentioning
confidence: 98%
“…They claimed a 27% ''cure'' rate with psychoanalysis, but when challenged a decade later to produce a ''cured'' patient, they were unable to do so (Tripp, 1987). 27 Although practitioners of aversion therapy in the 1960s also claimed ''cures,'' by the 1970s behavioral therapists admitted that few of their patients managed to stay ''converted'' for very long (Bancroft, 1974;Davison, 1976).…”
Section: Homosexuality As Psychiatric Diagnosismentioning
confidence: 98%
“…Davison (1976) argued that the willingness of psychotherapists to try to modify sexual desire was related to their own views of homosexuality as pathology and served to support societal stigma. He suggested that mental health professions only added to the distress experienced by same-sex-attracted individuals as a consequence of societal prejudice and called for an end to 'change-of-orientation' clinical and research programmes.…”
Section: The Species Scriptmentioning
confidence: 99%
“…Little if any time was spent by mainstream therapists, regardless of theoretical orientation, encouraging health professionals to change their biases against homosexuality and foster gay-affirmative attitudes and behavior in patients who happened to be homosexual, and to treat the problems that homosexual individuals have rather than the so-called problem of homosexuality. The question for me many years ago (Davison, 1974(Davison, , 1976(Davison, , 1978(Davison, , 1991 was (and still is) the following: How can therapists honestly speak of nonprejudice when they participate in therapy regimens that, by their very existence and regardless of their effectiveness, condone a societal prejudice and perhaps also impede social change? The question of whether one can alter another's sexual preference is separate from the political and ethical issue of whether one should, though this distinction often has gone unappreciated by critics of my position (e.g., Sturgis & Adams, 1978).…”
mentioning
confidence: 99%